Enteric short‐chain fatty acids promote proliferation of human neural progenitor cells. Issue 6 (18th December 2019) - Yang, Liu L.; Millischer, Vincent; Rodin, Sergey; MacFabe, Derrick F.; Villaescusa, Juan C.; Lavebratt, Catharina
Abstract: Short‐chain fatty acids (SCFAs) are a group of fatty acids predominantly produced during the fermentation of dietary fibers by the gut anaerobic microbiota. SCFAs affect many host processes in health and disease. SCFAs play an important role in the 'gut‐brain axis', regulating central nervous system processes, for example, cell–cell interaction, neurotransmitter synthesis and release, microglia activation, mitochondrial function, and gene expression. SCFAs also promote the growth of neurospheres from human neural stem cells and the differentiation of embryonic stem cells into neural cells. It is plausible that maternally derived SCFAs may pass the placenta and expose the fetus at key developmental periods. However, it is unclear how SCFA exposure at physiological levels influence the early‐stage neural cells. In this study, we explored the effect of SCFAs on the growth rate of human neural progenitor cells (hNPCs), generated from human embryonic stem cell line (HS980), with IncuCyte live‐cell analysis system and immunofluorescence. We found that physiologically relevant levels (µM) of SCFAs (acetate, propionate, butyrate) increased the growth rate of hNPCs significantly and induced more cells to undergo mitosis, while high levels (mM) of SCFAs had toxic effects on hNPCs. Moreover, no effect on apoptosis was observed in physiological‐dose SCFA treatments. In support, data from q‐RT PCR showed that SCFA treatments influenced the expression of the neurogenesis, proliferation, and apoptosis‐related genes ATR, BCL2, BID, CASP8, CDK2, E2F1, FAS, NDN, and VEGFA . To conclude, our results propose that SCFAs regulates early neural system development. This might be relevant for a putative 'maternal gut‐fetal brain‐axis'. Cover Image for this issue: doi: 10.1111/jnc.14761 . Abstract : Short‐chain fatty acids (SCFAs) in the human body are produced mainly by anaerobic bacteria in the gut from their fermentation of dietary fibers. They signal through the free fatty acid receptors 2/3 (FFAR2/3). Our results showed that SCFAs at physiological levels increased the proliferation of human neural progenitor cells (hNPCs) and affected the expression of proliferation related genes. This finding proposes that SCFAs can regulate early human neural system development, which might be relevant for a putative 'maternal gut‐fetal brain‐axis'. Cover Image for this issue: doi: 10.1111/jnc.14761 .